Innovative Strategies for Vocabulary Acquisition: Integrating Suggestopedia and Word Search Games in EFL Classrooms - Selfin Jesika Loblobly; Nursalim (TEKILA: Journal of Language Teaching and Literature, 2025)
Vocabulary acquisition remains a significant challenge for many junior high school students in English as a Foreign Language (EFL) context. This study aims to examine the effectiveness of integrating the Suggestopedia method and Word Search Games in improving students’ vocabulary mastery. The research employed a pre-experimental one-group pretest–posttest design involving 20 seventh-grade students from class VII B at SMP Negeri 3 Kota Sorong. Data were collected through a vocabulary test consisting of 20 items focusing on verb-related vocabulary administered before and after the treatment. The collected data were analyzed using SPSS through descriptive statistics and a paired sample t-test. The results showed a clear improvement in students’ vocabulary achievement. The mean score increased from 60.00 in the pre-test to 79.75 in the post-test, indicating a substantial improvement after the implementation of the instructional strategy. The paired sample t-test produced a significance value of 0.000 (p < 0.05), demonstrating a statistically significant difference between the pre-test and post-test scores. These findings indicate that the integration of Suggestopedia and Word Search Games effectively improves students’ vocabulary acquisition. The results suggest that combining a relaxed learning environment through Suggestopedia with interactive game-based activities such as Word Search Games can support vocabulary learning in EFL classrooms. This integrated approach encourages student participation and facilitates repeated exposure to target vocabulary. Therefore, the study concludes that the combined use of Suggestopedia and Word Search Games provides an effective alternative strategy for vocabulary instruction in junior high school EFL contexts.